Anti-proliferative, anti-inflammatory and anti-mutagenic activities of a Prunus mahaleb L. anthocyanin-rich fruit extract. (December 2016) - Gerardi, Carmela; Frassinetti, Stefania; Caltavuturo, Leonardo; Leone, Antonella; Lecci, Raffaella; Calabriso, Nadia; Carluccio, Maria Annunziata; Blando, Federica; Mita, Giovanni
Highlights: Prunus mahaleb fruit concentrated extract ( mfce ) mediates health promoting effects. Mfce exhibits pro-apoptotic effect and modulates GJIC in MCF-7 cells. Mfce reduces vascular inflammation in human endothelial cells. Mfce shows anti-mutagenic effect on yeast Saccharomyces cerevisiae . Mfce could be a new source of functional food ingredients. Abstract: Prunus mahaleb L. is a marginal fruit crop producing cherry-like dark purple drupes with a very bitter taste, rich in polyphenolic compounds. A mahaleb fruit concentrated extract ( mfce ) has been assayed for its biological activities. In this work, we report results on the in vitro effects of mfce including: i) anti-proliferative, gap junction intercellular communication (GJIC) modulation and pro-apoptotic properties in a breast cancer cell line (MCF-7), ii) anti-inflammatory properties in human vascular endothelial cells (HUVEC), iii) anti-mutagenic effect on yeast Saccharomyces cerevisiae strain D7. Mfce exerted a dose-dependent anti-proliferative effect on MCF-7 cells together with a significant time-dependent increase in GJIC and a pro-apoptotic effect. Furthermore, mfce significantly reduced levels of endothelial inflammatory antigens in a concentration-dependent manner. Finally, mfce protected S. cerevisiae cells against H2 O2 cytotoxicity by direct radical scavenging activity. This study demonstrated multiple healthful biological effects of mfce, highlighting it as a potential nutraceutical product.